2014
DOI: 10.1103/physrevlett.112.096805
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Induced Pseudomagnetic Fields in Twisted Graphene Nanoribbons

Abstract: We present, for the first time, an atomic-level and quantitative study of a strain-induced pseudomagnetic field in graphene nanoribbons with widths of hundreds of nanometers. We show that twisting strongly affects the band structures of graphene nanoribbons with arbitrary chirality and generates well-defined pseudo-Landau levels, which mimics the quantization of massive Dirac fermions in a magnetic field up to 160 T. Electrons are localized either at ribbon edges forming the edge current or at the ribbon cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 47 publications
2
64
0
2
Order By: Relevance
“…In summary, we discover an extraordinary inductor performance of a nanostructure naturally occurring, unlike earlier hypothetical examples [36][37][38] , as a screw dislocation in graphitic carbons, e.g. in coal 8 .…”
Section: Br Whenmentioning
confidence: 95%
“…In summary, we discover an extraordinary inductor performance of a nanostructure naturally occurring, unlike earlier hypothetical examples [36][37][38] , as a screw dislocation in graphitic carbons, e.g. in coal 8 .…”
Section: Br Whenmentioning
confidence: 95%
“…The helicoid geometry creates a pseudo-electric field and this unexpected result is intriguing in view of the typical effect distortion has on graphene honeycomb lattice, that is to induce a pseudo-magnetic field, which leads to the valley-dependent edge states 17 . One possible reason for not observing pseudo-magnetic fields here is that the helicoid is a minimal surface (the mean curvature is zero everywhere), that is, it is curved but at the same time minimizes the surface energy, therefore not straining the underlying lattice.…”
Section: Avadh Saxenamentioning
confidence: 99%
“…[1][2][3][4] Interestingly, application of strain at the nanoscale provides an ideal way to locally tune material properties as desired for various optoelectronic device applications. 6 Similarly, it has been found that electronic properties of 2D materials are also affected by the presence of wrinkles in the 2D materials obtained by exfoliation or chemical vapor deposition (CVD) technique. 6 Similarly, it has been found that electronic properties of 2D materials are also affected by the presence of wrinkles in the 2D materials obtained by exfoliation or chemical vapor deposition (CVD) technique.…”
mentioning
confidence: 99%